2015
DOI: 10.5897/ajest2014.1793
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selected wetland plants for removal of chromium from tannery wastewater in constructed wetlands, Ethiopia

Abstract: Wastewater from leather processing industries is very complex and leads to water pollution if discharged untreated, especially due to its high organic loading and chromium content. In this study, the phytoremediation efficiency of selected wetland plant species in subsurface flow (SSF) constructed wetlands receiving tannery wastewater was investigated. Four pilot units were vegetated with Cyprus alternifolius, Typha domingensis, Parawaldeckia karaka and Borassus aethiopum and a fifth unit was left as unvegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Interestingly, maize plants accumulated a relatively higher Cr content in the roots than cowpea plants. This may explain the low translocation to the shoots, considering that the Cr fraction bound to root cells cannot be translocated to the shoots and, therefore, could not be removed in the shoot biomass harvest (Terfie & Asfaw, 2015). Hossner, Loeppert, Newton, and Szaniszlo (1998) reported that dicotyledon species, such as cowpea, uptake and transport more Cr to shoots than monocotyledons, such as maize.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, maize plants accumulated a relatively higher Cr content in the roots than cowpea plants. This may explain the low translocation to the shoots, considering that the Cr fraction bound to root cells cannot be translocated to the shoots and, therefore, could not be removed in the shoot biomass harvest (Terfie & Asfaw, 2015). Hossner, Loeppert, Newton, and Szaniszlo (1998) reported that dicotyledon species, such as cowpea, uptake and transport more Cr to shoots than monocotyledons, such as maize.…”
Section: Resultsmentioning
confidence: 99%
“…93.3% 69.7 -98,.0% 94.8 -95.4% 69.2 -92.3% 85.3 -89.1% 98.5 -98.7% 92.8 -98.7% 95.5 -96% 93.1 -96.2%. AYAZ et al, 2020 Efficiency of the system, bacterial inoculation with the desired traits has appeared as an effective option (TADESSE et al, 2015) they compared the performance of four macrophytes, Brachia mutica, Typha domingensis, Phragmites australis, and Leptochala fusca, in bacterial-assisted floating treatment wetlands for the purification of five metals (Fe, Mn, Ni, Pb, and Cr) from contaminated river water.…”
Section: Laurence Et Al (mentioning
confidence: 99%
“…These metals can accumulate in aquatic organisms and be magnified through food chains and eventually affect human health. The macrophage species Typha latifolia, Hydrilla verticillate and, Eichhornia crassipes have been used in surface flow wetlands, eliminating up to 23% of the Zn content TADESSE et al (2015). XIN et al (2020), SCHUCK and GREGER (2020) andWANG et al…”
mentioning
confidence: 99%
“…Unique due to its C4 photosynthetic pathway (Mnaya et al, 2007) -->98% (Kansiime and Mwesigye, 2012;Abou-Elela et al, 2014) Kenya (Vymazal, 2013); Ethiopia (Tadesse, 2010); Uganda (Okurut et al, 1999;Kansiime and Mwesigye, 2012).…”
Section: Cyperus Papyrusmentioning
confidence: 99%